PENGARUH AROMATERAPI BITTER ORANGE TERHADAP NYERI DAN KECEMASAN FASE AKTIF KALA 1 - Wiji Astuti; Heni Setyowati Esti Rahayu; Kartika Wijayanti (Universitas Muhammadiyah Semarang, 2015)
Background: Pain delivery is response to stimulation caused by contractions of the uterus and tissue damage during labor and vaginal delivery. Labor pain can cause stress which causes excessive release of hormones such as catecholamines and steroids. These hormones may cause smooth muscle tension and vasoconstriction of blood vessels. Another problem that arises during labor that is anxiety. Therapies to treat pain and anxiety during childbirth them using bitter orange aromatherapy. Aromatherapy bitter orange is treatment with aroma that can cause the body to relax. Objective: to determine the effect of bitter orange aromatherapy to pain and anxiety in women giving birth in the hospital when one Aisyiyah Magelang regency. Methods: The study design is Quasy experimental design with two group pretest-posttest control group design with Wilcoxon test and Mann Whitney test. Results: there is a difference between bitter orange aromatherapy to reduce the pain and anxiety of the mother when delivery in the first of the active phase with an average difference of 2.33 pain and anxiety differences in average 10.95 before and after given aromatherapy intervention group with p value = 0.000. Aromatherapy bitter orange can be used to reduce the maternal pain and anxiety in the active phase.Keywords: pain labor, anxiety, bitter orange.